Association of the PINX1 Variant rs6984094, Which Lengthens Telomeres, with Systemic Lupus Erythematosus Susceptibility in Chinese Populations - Yuan-yuan Qi; Xin-ran Liu; Ying-xin He; Min Zhou; Xiang-hui Ning; Ya-ling Zhai; Xiao-xue Zhang; Xiao-yang Wang; Ya-fei Zhao; Yan Cui; Zhan-Zheng Zhao (Journal of Immunology Research)
A recent genome-wide association study (GWAS) of Asian ancestry reported that single nucleotide polymorphism (SNP) in TERT (telomerase reverse transcriptase) was associated with systemic lupus erythematosus (SLE). TERT has a critical role in maintaining the chromosomal stability and the length of telomere. Given that only a small portion of the genetic heritability of SLE has been explained so far, we aimed to identify novel loci in telomere-related genes responsible for SLE susceptibility in Chinese populations. We performed a comprehensive genetic association analysis of SLE with telomere-related genes. To identify functional significance, we analyzed the publicly available HaploReg v4.1 and RegulomeDB databases. Differential gene expression analysis was also performed using ArrayExpress. A novel signal of PINX1 rs6984094 was identified (Pdiscovery=4.13×10−2, OR=0.58, 95% CI 0.35-0.98) and successfully replicated (Preplication=5.73×10−3, OR=0.45, 95% CI 0.26-0.81). Multiple layers of functional analysis suggested that the PINX1 rs6984094 risk T allele exhibited increased nuclear protein binding. We also observed an increased expression of PINX1 mRNA in peripheral blood mononuclear cells from SLE patients compared with healthy controls. Overall, we observed a novel genetic association between PINX1 (encodes the PinX1 protein, an inhibitory telomerase enzyme that lengthens telomeres) and SLE susceptibility in Chinese populations.